PARATHYROID CARCINOMA - Ahmad, Sajjad; Mufti, Tariq Saeed; Khan, Amjad A; Ahmad, Shakil (Journal of Ayub Medical College Abbottabad, 2006)
Parathyroid carcinoma is a very rare cause of primary hyperparathyroidism and these tumors are usually hyper-functioning as compared to other malignant endocrine tumors. Surgery is the only effective primary treatment. We report a patient, who presented with pathological fracture of femur, hypercalcemia, bilateral renal stones, markedly raised Parathormone levels and palpable mass in the neck. Parathyroid adenoma was initially diagnosed and localized at left lower gland by Sestamibi scan and ultrasonography. She underwent surgery and enlarged parathyroid gland was removed. Intra operatively there was no evidence of local invasion or lymph nodes involvement but biopsy report suggested malignancy. Keywords: Parathyroid carcinoma, Adenoma, Primary hyperthyroidism, Sestamibi scan.